Ecological Sensing Through Taste and Chemosensation Mediates Inflammation: A Biological Anthropological Approach. Issue 6 (10th July 2020) - Giuliani, Cristina; Franceschi, Claudio; Luiselli, Donata; Garagnani, Paolo; Ulijaszek, Stanley
ABSTRACT: Ecological sensing and inflammation have evolved to ensure optima between organism survival and reproductive success in different and changing environments. At the molecular level, ecological sensing consists of many types of receptors located in different tissues that orchestrate integrated responses (immune, neuroendocrine systems) to external and internal stimuli. This review describes emerging data on taste and chemosensory receptors, proposing them as broad ecological sensors and providing evidence that taste perception is shaped not only according to sense epitopes from nutrients but also in response to highly diverse external and internal stimuli. We apply a biological anthropological approach to examine how ecological sensing has been shaped by these stimuli through human evolution for complex interkingdom communication between a host and pathological and symbiotic bacteria, focusing on population-specific genetic diversity. We then focus on how these sensory receptors play a major role in inflammatory processes that form the basis of many modern common metabolic diseases such as obesity, type 2 diabetes, and aging. The impacts of human niche construction and cultural evolution in shaping environments are described with emphasis on consequent biological responsiveness.